Effects of Lactobacillus buchneri as a silage inoculant and as a probiotic on feed intake, apparent digestibility and ruminal fermentation and microbiology in wethers fed low-dry-matter whole-crop maize silage - Rabelo, C. H.S. [UNESP]; Basso, F. C. [UNESP]; Lara, E. C. [UNESP]; Jorge, L. G.O. [UNESP]; Härter, C. J. [UNESP]; Mesquita, L. G.; Silva, L. F.P.; Reis, R. A. [UNESP] (Wiley, 2018)
Lactobacillus buchneri was investigated as a silage inoculant and as a probiotic on feed intake, apparent digestibility, and ruminal fermentation and microbiology in wethers fed low-dry-matter (DM) whole-crop maize silage. Maize forage (279 g/kg DM) was ensiled without inoculant (untreated) and with L. buchneri CNCM I-4323 at 1 × 105cfu/g fresh forage (inoculated). Six cannulated wethers were arranged in a double 3 × 3 Latin square and assigned to one of three diets: (i) untreated maize silage (untreated), (ii) inoculated maize silage (inoculated), and (iii) untreated maize silage with a daily dose of L. buchneri (1 × 107cfu/g supplied silage) injected directly into the rumen (LB-probiotic). Wethers fed the inoculated diet had a higher (p =.050) DM intake (1.30% body weight [BW]) than wethers fed untreated and LB-probiotic diets (1.17% and 1.18% BW respectively). The relative proportion of Ruminococcus flavefaciens (proportion of total estimated rumen bacterial 16S rDNA) in the rumen of wethers fed inoculated and LB-probiotic diets (both 0.42%) tended (p =.098) to be lower than in the untreated diet (0.83%). Lactobacillus buchneri as a silage inoculant or as a probiotic had little effect on the variables measured in wethers.
Keywords: corn silage; lactic acid bacteria; nutritive value; ruminal bacterial community; volatile fatty acid